The effect of oil-heat treatment on biological durability of acacia mangium wood - Illya Nur Syazwanie Ahmad Mazalan (2017)
Durability of treated Acacia mangium’s wood was investigated by using laboratory test. Acacia mangium were harvested then divided into three parts, which top, middle and bottom. Heat treatment method by using crude cooking oil with temperature (180oC, 200oC and 220oC) and duration of treatment (30, 60 and 90 minutes) were carried out to treat the Acacia mangium’s wood. The physical and durability of wood were tested in accordance with ISO standard. Durability of wood was tested by exposing the wood to three types of fungi Coriolus versicolors, Gloeophyllum trabeum and Pycnoporus sanguineus for 12 weeks. The untreated Acacia mangium’s wood used as control sampes for this study. The results showed that heat treatment improved the durability of Acacia mangium. The Coriolus versicolors fungal attack of treated Acacia mangium’s wood were decreased compared to the control samples which is from 11.48% (bottom), 14.27% (middle) and 15.69% (top) to 1.87% -10.19% at the bottom, 3.10% - 12.69% in the middle and 4.78% - 15:20% on top. The decreasing of fungal attack also occurred to the wood that being exposed to the Gloeophyllum trabeum from 5.02% at the bottom, 22.5% in the middle, 5.72% on the top for control sample to 0.54% - 4.55% (bottom), 0.91% - 4.41% (middle) 1.08% -4.38% (top). Durability of Acacia mangium’s wood after oil heat treatment against Pycnoporus sanguineus fungal attack also increased based on the decreasing percentage of fungal attack on wood, which is 10.53% (bottom), 18.24% (middle), 18.73% (top) to 3.71% - 10.18% (bottom), 5.74 % -% 14:59 (middle) and 4:37% - 17.8% (top). Images obtained by scanning electron microscopy also showed the fungal attack was higher on untreated wood where heavy colonization of mycelia occurs in untreated wood vessels compared with the treated wood.